Digitalisasi Daerah: Implementasi Pelayanan Publik Di Kota Semarang Berbasis Smart City Dimensi Smart Government - Galang Zukhrian Warsdapama; Nurmandi, Achmad; Fridayani, Helen Dian (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The plusblems raised in this study are related to the implementation of smart city policies with smart government dimensions in realizing public services that focus on the use of information and communication technology through the internet, online, digital and social media . The research method used is a descriptive method with a qualitative applusach. The results showed that the implementation of mart city in realizing public services with smart government dimensions in Semarang city into 3 indicators, namely: 1) public services, with various applications and websites of public services for the community; 2) Infrastructure, which is integrated with various fields to facilitate services; 3) government openness, as a medium of transparency and accountability to government performance for the community.